Use of Simulation to Enhance Learning in a Pediatric Elective - Tofil, Nancy M. (American Journal of Pharmaceutical Education, 2010)
OBJECTIVES: To assess the impact on learning of adding a pediatric human patient simulation to a pharmacy course. DESIGN: Pharmacy students enrolled in a pediatric elective participated in 1 inpatient and 1 outpatient scenario using a pediatric patient simulator. Immediately following each case, reflective debriefing occurred. ASSESSMENT: Forty-two students participated in the simulation activity over 2 academic years. A pretest and posttest study design was used, with average scores 4.1 ± 1.2 out of 9 on pretest and average 7.0 ± 1.5 out of 9 on posttest (p < 0.0001). Ninety-five percent (40/42) of students' scores improved. Students felt the learning experiences were positive and realistic. CONCLUSIONS: Pharmacy students' knowledge and application skills improved through use of pediatric simulation exercises.